Optimisation of ultrasound treatment to enhance the postharvest life of fresh-cut pineapple - Yeoh, Wei Keat (2017)
Minimal processing of fresh-cut pineapple (Ananas comosus L.) is time and labour consuming as it has thick inedible skin and large crown. Liberation of cellular contents at the site of wounding can promote the growth of microorganisms and limit the storage life of fresh-cut pineapple. Therefore, ultrasound treatment at different power input and exposure time was used to investigate its effectiveness on the storage life of fresh-cut pineapple. To determine the antimicrobial effect of ultrasound on the proliferation of spoilage microorganisms three different ultrasound power inputs (17, 25 and 29 W) and treatment times (5, 10 and 15 min) during 7 days of storage at 7 oC were applied on co. Josapine. The application of ultrasound at the power input of 25 and 29 W for 10 and 15 min, respectively, inhibited the growth of mesophilic, lactic acid bacteria and yeast and moulds. On day 5, it was found that 29 W for 15 min treatment resulted in the lowest growth of mesophilic, lactic acid bacteria and yeast and mould counts. However, changes in the proliferation of spoilage microorganism were observed among samples treated at 25 W: 10 min, 25 W: 15 min and 29 W: 10 min. The storage life of ultrasound treated fresh-cut pineapple was extended by 2 days in comparison to those washed in distilled water (dH2O).